Towards a sustainable fashion industry: Determinants to French millennials’ buying intention of second-hand clothes - Bertout, Caroline (2022)
The Covid-19 health pandemic fostered the awareness and the motivations towards a more sustainable consumption. This quantitative study analyses the conditioning factors of the second-hand clothes purchase by the French Millennials, as they are currently an active generation. Its main objective is to understand this specific population’s buying intention of second-hand clothes, and the underlying motivations and barriers. Those determinants might differ compared to previous studies, because of the generation, the localisation and the time period studied. Therefore, the research is meant to provide additional academic knowledge. The aim is also to give insights on consumers’ behaviour and recommendations to companies, to help them seize the second-hand market opportunity. It is intended to consumers as well, to educate them about sustainable consumption practices. To conduct this study, a quantitative approach has been used. An online questionnaire was shared on social medias. Following a convenience sample methodology, a total of 94 participants, consumers as well as non-consumers of used clothing, took part in the research. The findings reveal that French millennials have a positive buying intention towards second-hand clothes. Economic and ethical motivations have a great positive effect on buying intention, while fashion factors don’t. On the other hand, utilitarian and self-expression determinants impact negatively the buying intention, whereas the affiliation barrier doesn’t have an influence and seems to fade away. Even though the findings can’t be generalized, they can be used for future researches.